Biomechanical constitutive modeling of the gastrointestinal tissues: A systematic review. (May 2022) - Patel, Bhavesh; Gizzi, Alessio; Hashemi, Javad; Awakeem, Yousif; Gregersen, Hans; Kassab, Ghassan
Graphical abstract: Highlights: Biomechanical constitutive models of gastrointestinal tissues were cross-analyzed. Microstructural models that provide actual structure–function relations are scarce. Coupled electro-mechanical models including active muscle contractions are lacking. Models based on human data under physiological and pathological conditions are needed. Abstract: The gastrointestinal (GI) tract is a continuous channel through the body that consists of the esophagus, the stomach, the small intestine, the large intestine, and the rectum. Its primary functions are to move the intake of food for digestion before storing and ultimately expulsion of feces. The mechanical behavior of GI tissues thus plays a crucial role for GI function in health and disease. The mechanical properties are characterized by a biomechanical constitutive model, which is a mathematical representation of the relation between load and deformation in a tissue. Hence, validated biomechanical constitutive models are essential to characterize and simulate the mechanical behavior of the GI tract. Here, a systematic review of these constitutive models is provided. This review is limited to studies where a model of the strain energy function is proposed to characterize the stress–strain relation of a GI tissue. Several needs are identified for more advanced modeling including: 1) Microstructural models that provide actual structure–function relations; 2) Validation of coupled electro-mechanical models accounting for active muscle contractions; 3) Human data to develop and validate models. The findings from this review provide guidelines for using existing constitutive models as well as perspective and directions for future studies.